A Comparison of Magnetic Resonance Imaging Assessment and Biopsy Outcomes with and Without Central Review in Two Swedish Regional Organized Prostate Cancer Testing Programs - Jonas Wallström; Max Alterbeck; Rebecka Arnsrud Godtman; Ola Bratt; Thomas Jiborn; Erik Thimansson (European Urology Open Science, 2025)
Background and objective: The European Council advises evaluating the feasibility of organized prostate cancer testing (OPT) programs, but it is unclear whether results from screening trials can be replicated in population-based testing. The aim of this study is to compare magnetic resonance imaging (MRI) assessments and biopsy outcomes with and without a central review in two Swedish OPT programs. Methods: Two regional population-based OPT programs invited 65 000 men (2020–2022). MRI scans were read locally, and biopsies followed a strict MRI-based and prostate-specific antigen (PSA) density–based protocol. A blinded central review was done by two radiologists with 8 and 9 yr of experience. Reader agreement was assessed with percentages and kappa scores. Positive predictive values (PPVs) for detecting grade group (GG) 2–5 prostate cancer were calculated with 95% confidence intervals (CIs). Key findings and limitations: MRI scans for 416 men (median age 52 yr) with PSA ≥3 ng/ml were evaluated. In Skåne, 27% of scans were primarily assigned Prostate Imaging Reporting and Data System (PI-RADS) scores ≥4, compared with 10% in Västra Götaland. At the primary reading, 76 men had PI-RADS ≥4, yielding 43 GG 2–5 prostate cancer cases: PPV 0.57 (95% CI 0.45–0.67). At the central review, 65 men had PI-RADS ≥4. Out of 61 men biopsied, 50 had GG 2–5 prostate cancer: PPV 0.82 (95% CI 0.71–0.90, p < 0.001 for PPV difference). The central review radiologists’ kappa score was 0.83. No additional biopsies were taken based on the central review findings. Conclusions and clinical implications: In population-based screening with local MRI reading, MRI assignment may vary substantially. Centralized reading could reduce these differences and increase the biopsy PPV for GG ≥2 cancer. Patient summary: In this report, we reviewed local magnetic resonance imaging (MRI) reading in population-based screening. We found that MRI assignment varied between centers. We conclude that centralized reading could reduce differences and improve biopsy outcomes.